Endothelial METTL3 (Methyltransferase-Like 3) Inhibits Fibrinolysis by Promoting PAI-1 (Plasminogen Activator Inhibitor-1) Expression Through Enhancing Jun Proto-Oncogene N6-Methyladenosine Modification. Issue 12 (14th October 2021) - Bai, Qin; Lu, Yao; Chen, Yanhua; Zhang, Han; Zhang, Weiwei; Wu, Huang; Wen, Aiqing
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: METTL3 (methyltransferase-like protein 3)-mediated N 6 -methyladenosine modification is the most abundant RNA modification on eukaryote mRNAs and plays a crucial role in diverse physiological and pathological processes. However, whether N 6 -methyladenosine modification has function in thrombosis is unknown. This study aims to determine the role of METTL3 in the endothelial cells-mediated thrombosis. Approach and Results: RNA-sequencing and real-time quantitative PCR revealed that the expression of PAI-1 (plasminogen activator inhibitor-1) was downregulated in METTL3 knockdown human umbilical vein endothelial cells. In vitro experiments showed that METTL3 suppressed fibrinolysis. Mechanically, RNA methylation sequencing and meRIP-quantitative real-time PCR showed that METTL3 catalyzed N 6 -methyladenosine modification on 3′ UTR of JUN mRNA. Western blotting analysis showed that METTL3 promoted JUN protein expression. Chromatin immunoprecipitation analysis demonstrated that JUN bound to the PAI-1 promoter in human umbilical vein endothelial cells. Furthermore, mice challenged with lipopolysaccharide resulted in higher METTL3 expression in vessels. Endothelial-specific knockdown of Mettl3 decreased expression of active PAI-1 in plasma and attenuated fibrin deposition in livers and lungs during endotoxemia. Conclusions: Our study reveals that METTL3-mediated N 6 -methyladenosine modification plays a crucial role in fibrinolysis and is an underlying target for the therapy of thrombotic disorders.